2017
DOI: 10.14738/abr.58.3563
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Marketing Mix On Student Trust and Its Impact on Competitive Advantage Of Private Higher Education Institution

Abstract: The purpose of this research is to construct a new concept about the influence of marketing mix to trust and trust towards the competitive advantage of private higher education. The research method of gathering data in this research is by conducting quantitative research. The dissemination of the survey is using simple random sampling at private higher education in Kepulauan Riau (Kepri) province of Indonesia. Respondents from this research are 425 students representing all students of private higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The study results showed that promotion significantly affects trust (Kim et Sama et al, 2017). Likewise, the study results showed that promotion significantly affects customer satisfaction (Hatta et al, 2018;Pi & Huang, 2011;Kim et al, 2014).…”
Section: Promotionsmentioning
confidence: 97%
See 1 more Smart Citation
“…The study results showed that promotion significantly affects trust (Kim et Sama et al, 2017). Likewise, the study results showed that promotion significantly affects customer satisfaction (Hatta et al, 2018;Pi & Huang, 2011;Kim et al, 2014).…”
Section: Promotionsmentioning
confidence: 97%
“…Several study results show that price significantly affects trust (Kim et al, 2014;Hikmawati, 2015;Maulana et al, 2021;Thalib, 2015;Quareshi, 2015). Price also significantly affects satisfaction (Pardiyono, 2020;Radiman et al, 2018;Basyouni, 2019;Surya, 2019;Sama et al, 2017;Alipour et al, 2012).…”
Section: Pricementioning
confidence: 98%
“…White (2018) examines relations of authority and trust between students and academic teachers from the viewpoint of student partnership; the partnership is an element with a strong positive relation to the students" trust. Sama, Brahmasari & Ratih (2017) introduce a concept that studies the influence of marketing mix to trust and trust towards the competitive advantage of private higher education.…”
Section: Introductionmentioning
confidence: 99%